Iranian medical students’ EFL writings anxiety, coping strategies, and attitudes towards writing in an online setting - Zargar, Mohsen; Nimehchisalem, Vahid (Scientific Research Publishing, 2023)
To make stronger claims about the function of anxiety in online setting and its interaction with writing performance, there is a need to carry out extensive studies in various settings and with participants of different background experiences. Hence, this mixed method study set out to examine the effect of E-learning of English writing on Iranian medical students’ writing anxiety and writing attitude. Students’ sources of writing anxiety and coping strategies were also explored. To achieve the objectives, 71 upper-intermediate and advanced level Iranian medical students from Semnan, Iran, were recruited. In the quantitative phase, the required data were collected by employing two adapted questionnaires, namely, Writing Attitude and Second Language Writing Anxiety Inventory. In the qualitative phase, nine participants were interviewed. The results revealed that after receiving the online instruction, the students’ writing anxiety decreased while their attitudes became more positive. Regarding the qualitative data analysis, “technical issues”, “lecturer”, and “time management” were the most prevalent sources of writing anxiety, and “staying calm and relaxed”, “focusing on the given topic”, and “preparing in advance” were mentioned as the most prevalent coping strategies amongst the students. The findings have useful pedagogical implications.